2014
DOI: 10.1007/s13277-014-2327-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitidine chloride induces apoptosis, cell cycle arrest, and synergistic cytotoxicity with doxorubicin in breast cancer cells

Abstract: Medicinal plant extracts have been widely used for cancer treatment. Nitidine chloride (NC) is a natural bioactive alkaloid that has recently been reported to have diverse anticancer properties. We aimed to investigate the cytotoxic effects of NC and the effectiveness of combinatorial treatment including NC and doxorubicin in breast cancer cells. Using MTT and flowcytometry assays, we found that NC induced cell growth inhibition and G2/M cell cycle arrest in a time- and dose-dependent manner both in MCF-7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
3
36
0
1
Order By: Relevance
“…Another study revealed that NC exposure led to inhibition of cell proliferation and induction of cell cycle arrest through elevation of multiple gene expressions such as p53, p21, Bax, and active forms of caspase-3, caspase-9, and cleaved PARP, and downregulation of Bcl-2 [9]. Notably, NC sensitizes cell sensitivity to doxorubicin for cell proliferation in breast cancer [9].…”
Section: Breast Cancermentioning
confidence: 99%
“…Another study revealed that NC exposure led to inhibition of cell proliferation and induction of cell cycle arrest through elevation of multiple gene expressions such as p53, p21, Bax, and active forms of caspase-3, caspase-9, and cleaved PARP, and downregulation of Bcl-2 [9]. Notably, NC sensitizes cell sensitivity to doxorubicin for cell proliferation in breast cancer [9].…”
Section: Breast Cancermentioning
confidence: 99%
“…Bax, cleaved caspase-9 and -3 and cleaved PARP) and down-regulating anti-apoptotic proteins (e.g. Bcl-2 and PARP) [119,120] .…”
Section: Anticancermentioning
confidence: 99%
“…For other species of Orophea, O. uniflora is endemic in India whereas O. palawanensis is found in Philippines. Various bioactive alkaloids are extracted from medicinal herbs such as nitidine chloride from Zanthoxylum nitidum with anticancer effect against breast cancer cells (Sun et al, 2014). N-norchelerythrine and dihydrosanguinarine, from Broussonetia papyrifera (L.) Vent.…”
Section: Introductionmentioning
confidence: 99%